Unemployment and Youth Restiveness in Nigeria: Implications for Transforming the Economic Sector - ABONYI, Sunday Evaristus; ONWUKA, Chukwujekwu Charles; ARINDE-SIMEON, Titilayo Olamide; EZEH, Christian Igwebuike (Ilorin Journal of Education, 2023)
The paper examined the issue of unemployment and youth restiveness in Nigeria and the need for government and all stakeholders to rise up to their responsibilities in reshaping the economy and make the country a better and safer place. The increasing spate of unrest, insecurity, mass protest, demonstration, killings, looting, kidnapping, wanton destruction of properties and other social vices going on in Nigeria since the onset of democratic government in the country are not unconnected with unemployment. The paper relied more on review of relevant literature using internet, text-books, conference papers and policy documents. The paper painstakingly highlighted the nature and magnitude of unemployment in the country between 2011-2020 and the associated consequences/ such as mass uprising and protests. It further discussed the precipitating factors underlying the unemployment rate in Nigeria and then the implications to transforming the real sector of the economy. The author recommended among others, that the government should recognize the school curriculum towards vocational/skills acquisition that will enable youths become self-employed after completion of their educational programmes.